An investigation of online acoustic information for elite rowers in on-water training conditions - Schaffert, N.; Mattes, K.; Effenberg, A. O. (Journal of Human Sport & Exercise, 2011)
Presenting acoustic information has become increasingly interesting for technique training and control in various sports. In elite rowing, acoustic feedback is a new and promising application to optimize the boat's forward motion. This paper describes the potential of acoustic information which represents the movement-relevant information on the boat's forward motion for rowing and its implementation as online acoustic feedback during on-water training sessions. The first significant results were encouraging and support the intention to implement the acoustic information regularly into training processes for elite athletes.